Glucagon-like peptide 1 level and risk of death within 90 days after intensive care unit admission: A substudy of the IVOIRE cohort - Marine Jacquier; Annabelle Tavernier; Jean-Pierre Quenot; David Masson; Elea Ksiazek; Isabelle Fournel; Jacques Grober (PLoS ONE, 2025)
Background Elevated plasma levels of glucagon-like peptide-1 (GLP-1) have been associated with poor clinical outcome in patients with sepsis. This study investigated the association between GLP-1 levels, and survival at 90 days in a large cohort of critically ill patients. Methods All patients aged ≥ 18 years admitted to the intensive care unit (ICU) in a large university hospital, and receiving ≥1 life support therapy for organ failure were eligible for inclusion. Plasma samples were taken within 24h of ICU admission. We measured GLP-1 using a commercial ELISA kit. Cumulative probability of death at 90 days (D90) was plotted using the Kaplan-Meier method by quartiles of GLP-1. The effect of GLP-1 quartile on D90 survival was analyzed using a Cox proportional hazards model. Results A total of 507 patients had GLP-1 dosage; mean age 64.5 ± 14.5 years; 179 (35.3%) women. GLP-1 levels ranged from 0.03 to 129.2 (median 7.3[IQR:3.3;19.1]). Higher mean age, SOFA, SAPS II, and LPS 3HM were found in patients with higher GLP-1 quartile by univariate analysis. Overall, 229 patients (45.2%) died within 90 days. The cumulative probability of death was significantly associated with GLP-1 quartile (p log rank<0.0001). After adjustment for age, SOFA, renal replacement therapy and vasopressor treatment, a significantly increased risk was observed only for patients with the highest quartile of GLP-1 (adjusted hazard ratio 1.65 [1.06; 2.56] for 4th vs 1st quartile of GLP-1). Conclusion After adjusting for demographic and clinical characteristics, only the highest quartile of GLP-1 remained independently associated with an increased risk of death at 90 days after admission to ICU.